Penerapan Electronic Traffic Law enforcement (ETLE) Terhadap Pelanggaran Lalu Lintas Di Wilayah Hukum Polresta Padang - Oktara Roberto; Yandriza (Fakultas Hukum Universitas Andalas, 2023)
The very rapid development of technology has an impact on all sectors of human life. The development of this technology was utilized by the Indonesian National Police by creating an electronic ticketing system called electronic traffic law enforcement, abbreviated as ETLE. The implementation of ETLE aims to reduce the number of traffic violations, eliminate the phenomenon of illegal collection during enforcement and simplify the ticket enforcement process. The number of traffic violations in the city of Padang has increased significantly after the implementation of ETLE. In implementing ETLE, the Polresta Padang encountered several obstacles, such as a lack of public knowledge and a lack of public awareness regarding the renewal of the ticketing system through ETLE. This research uses empirical juridical research methods with descriptive research characteristics. The required data comes from primary data and secondary data taken from a study of documents and interviews at the Padang City Police Department. This ETLE ticketing system has been implemented in the city of Padang starting from March 24 2021 until now. The research results show that the implementation of the electronic traffic law enforcement ticketing system has not been fully implemented optimally. The implementation of ETLE is not yet optimal due to several obstacles such as the public's lack of knowledge of traffic regulations and the ETLE system, lack of facilities and infrastructure, social and cultural factors that are developing in the community and weaknesses in the system for identifying violating vehicles. This is still a fundamental factor causing the increase in traffic violations in the jurisdiction of the Polresta Padang.